Big Influence of Youth Fanaticism on South Korean Idol to Skincare’ Purchase Decision - Juniarti, Gita (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
This research aims to determine the influence of labels on skincare products from South Korea and the influence of fans' fanaticism on purchasing skincare products. In previous research, the halal and eco-green labels had a significant effect. On the other hand, previous research also stated that fanatical feelings in supporters or fans greatly influence purchase decisions. This research uses a quantitative approach. The population is young people in Gorontalo City who buy skincare products at cosmetic and skincare outlets in Gorontalo City. The sample was selected using nonprobability and accidental, namely young people who bought skincare at these outlets on 1-8 June 2023. The number of samples selected were 138 young people in Gorontalo City who shopped at Sashop, Guardian, and Erby Shop. Data analysis techniques use statistical tests of normality, multicollinearity, heteroscedasticity, and the coefficient of determination. The results show that the hypothesis is accepted. The coefficient of determination test on South Korea labels shows a value of 0.044, while fanaticism shows a value of 0.049. These values are smaller than 0.05. The result of the t count on the South Korean labels variable shows 9.157, while the fanaticism variable shows 7.070. The t-test results of the two variables have a value more than the t table, which is 1.980. The coefficient test and t-test showed that the South Korean labels and fanaticism variables significantly influence purchase decisions. The influence of the South Korea Labels variable is 9 per cent, while the fanaticism variable influences 61 per cent. It means there is 70 per cent influence by these two variables, and the other 30 per cent is influenced by other variables that need to be tested by future researchers.